The value of PET-CT scan in determining remission status in lymphoma patients involving the head & neck region - Wan Fariza Wan Jamaludin; Fara Rahidah Husin; Aini Ab. Aziz; Mohd Razif Mohd Yunus; Mawaddah Azman; Kong, Min Han; Noraidah Masir; Mahdieh Ghoddoosi; Seery Zaliza Azura Zaider; Normi Mustapha; Nor Asiah Muhamad; S Fadilah Abdul Wahid (Penerbit Universiti Kebangsaan Malaysia, 2019)
In lymphoma, Positron Emission Tomography-Computerized Tomography (PET-CT) provides greater prognostic information than conventional imaging. However, false positivity occurred particularly in the head & neck due to predilection for infection and inflammation. We investigated the association between positive scans in the head & neck at the end of therapy with histology, and its diagnostic and prognostic values. 488 PET-CT were retrospectively assessed in 2012-2016 (40 months). Positive uptakes in the head & neck (five-point scale ≥4) were biopsied. Prevalence of positive scans was 10.9% (53/488). Two positive scans were histologically lymphomatous with mean maximum standardized uptake value (SUVmax) of 9.0±2.69. False positivity (96.2%) was histologically attributed to reactive lymphoid hyperplasia (SUVmax 9.0±3.88). Positive and negative predictive values, sensitivity and specificity were 3.8%, 100%, 100% and 89.5%, respectively. False positivity was associated with age, gender, extra-nodal involvement, Eastern Cooperative Oncology Group score (ECOG), positivity only in the head & neck and its pattern of positivity. No significant predictors were identified. Hodgkin Disease (HD) was more likely to have positivity only in the head & neck compared to Non-Hodgkin Lymphoma (NHL) (p=0.019). 106 patients with negative scans remained negative during study period, hence regarded as true negatives. Positive scans in the head & neck at post therapy yielded high false positivity and should not be routinely performed. HD has higher likelihood of scan positivity only in the head & neck than NHL. The value of PET-CT to detect true lymphomatous relapse in selected high-risk patients remained to be confirmed in future trials.